The Concept of Gender in Cirebon Oral Literature and Its Transformation in the Memitu Slametan Rituals - Nurul Atikah Fauzi (Journal of World Science, 2024)
Cirebon oral literature, specifically tembung éntar, is an essential cultural resource that reflects societal values, particularly concerning gender roles. However, previous studies have not thoroughly examined how these expressions play out in ritual practices, highlighting a gap that this research seeks to fill. This study investigates the concept of gender found in tembung éntar and how it changes within the traditional ritual of Slametan Memitu. Employing a qualitative descriptive approach with semiotic analysis, 412 tembung éntar texts were analyzed. The data collection process involved documentation and analysis performed in four stages: gathering data, reducing it, presenting findings, and verifying the results. The findings showcase symbolic representations of gender roles in which tembung éntar indicates masculine and feminine qualities, including persistence, diligence, care, and obedience. The Slametan Memitu ritual transforms these symbolic meanings into cultural practices, illustrated by expressions such as “Asah, Asih, Asuh” and “Manek gunung temurub jurang,” which emphasize mutual support and resilience. This research offers a fresh perspective by connecting oral literature with ritual performance, stressing the cultural representation of gender roles. Upcoming studies could investigate similar transformations in different cultural settings.